Temper embrittlement of 9%Ni low carbon steel and nondestructive inspection by magnetic Barkhausen noise - Tavares Sérgio S.M. (EDP Sciences, 2021)
9% Ni and low carbon steel is used in cryogenic services in oil and gas industries. The final mechanical properties are adjusted by quenching and tempering heat treatments. However, the un-correct tempering may cause temper embrittlement, with drastic decrease of toughness at cryogenic temperatures. In this study, specimens tempered at 350°C, 400°C and 450°C showed very low toughness at low temperature (-196°C) due to temper embrittlement. Specimens slowly cooled from the tempering temperature (565°C, 585°C and 605°C) also showed toughness reduction in comparison with specimens tempered at the same temperature and cooled in water. The brittle fracture was characterized by intergranular cracks and cleavage. Magnetic Barkhausen Noise (MBN) inspection was conducted to verify if this technique can be used to detect the temper embrittlement in 9Ni steels. The root mean square (RMS) of the MBN signal was higher in specimens as quenched and in specimens tempered in the temper embrittlement range (350°C-500°C) than in specimens which were correctly tempered (565°C-605°C and water cooled). Comparing specimens tempered at 565 and 585°C range and slowly cooled with those which were water cooled, the RMS(MBN) was higher in the former group, which presented the lower toughness. However, the MBN inspection could not separate specimens tempered at 605°C slowly and rapidly, which can be related to the higher austenite volume fraction measured in the specimen slowly cooled.